The Development of GISEL Media (Giant Snakes and Ladders) in Social Class V Elementary School - Hardono, Sukmawati Dewi; Nurhasanagih, Ana; Yuliana, Rina (Jurnal Primagraha, 2020)
This study aims to determine how to develop gisel media (giant snakes and ladders) in social studies class V Elementary Schools, to determine the feasibility of giant gakes products (giant snakes and ladders) in social studies class V Elementary Schools that were developed get an assessment from experts , and to determine students' responses to giant snakes and ladders media products in social studies class V Elementary School. The type of research used in the research and development method of the Borg and Gall modified from Sugiyono consists of 6 stages: the problem analysis stage, the data collection stage, the product design development stage, the product design validation stage, the improvement test stage (revision) product design, and product trial phase. The results of the validation test by experts (media experts, material experts, linguists, and education experts) on the quality of gisel media (giant snakes and ladders) developed are included in the very feasible criteria with a percentage rating of 94.57%. The results of the trial are limited to students of giant snakes and ladders media who get very decent criteria with an assessment percentage of 97.60%. Based on the results of the study it can be concluded that the gisel media (giant snakes and ladders) developed are very feasible to be used in the learning process of Social Sciences (IPS).